Evolução do uso e ocupação dos sistemas ambientais de municípios costeiros do baixo Jaguaribe-Ceará (1984 -2016): aplicação de geotecnologias para subsidiar o ordenamento territorial - Oliveira, Huáscar Pinto Vidal de (2018)
The evolution of historical occupation of the coastal regions of Brazil has suffered from of a valorization process, intense and disorderly occupation which is associated to the process of globalization of the economy. In the last decades, the coast of the State of Ceará, specifically the coastal municipalities of Baixo Jaguaribe, has been the object of adaptations and transformations. The delimitation of environmental systems and their vulnerability to degradation allow a social and environmental diagnosis in view of the different pressures on a territory. These tools allow to contributes in this way to the territorial ordering, making possible the identification of places where these pressures can cause exacerbation of environmental degradation. The presente study aims to evaluate the spatio-temporal evolution of the use and occupation of the environmental system of the municipalities of Fortim, Aracati and Icapui, through geotechnologies capable of subsidizing land use planning. The research was based on systemic studies s and integrating knowledge, approch, that enabled the analysis of cause and effect interrelations, defining the sensitivity and the resistance of the environment in the face of land use. This research is structured in three phases: analysis phase including literature review, theoretical foundation, thematic mapping, geoprocessing of LANDSAT 5, 8 and SPOT 5 Satellites images with field control and thematic mapping; integration phase consists of the structuring, delimitation and characterization of the environmental systems correlating them with the current use and occupation and analysis of the time and spatial evolution (1984-2016) of the use and occupation of the environmental system. According to the results was obtained, in the definition of six environmental systems subdivided into eleven sub-systems such as: coastal plain, fluvial plains, pre-coastal sedimentar deposit, Apodi Plateau, crystalline residual massifs and sertaneja depression. We defined three classes and twenty-three mapped subclasses of the use and occupation of environmental systems. The analysis of the evolution of the landscape of the coastal municipalities of the low Jaguaribe in the interval of thirty two-years it was verified several changes produced by the socioeconomic activities. The coastal plain, which is the most unstable environmental system with high vulnerability to occupation, covering more than half of the entire area, evidencing the following changes: 1. Marine fluvial plain of the Jaguaribe, installation and expansion of shrimp farming; expansion in the occupation of mobile dunes, semi-fixed dunes; expansion of agroextractivism areas; 2. Fluvial plains expansion in the class of agroextractivism; 3. pre-coastal sedimentar deposit present low vulnerability to occupancy due to stable ecodynamic condicions and showing potential for urban expansion and increase of agroextratism and horticulture implementation in the municipalities of Aracatí and Icapuí. The results demonstrate the importance of integrated studies with support for geotechnology instruments, supporting territorial physical diagnoses, as well as for understanding the evolution verified over the years. In this way, the study made possible the temporo-spatial evaluation of environmental systems, the conditions that allowed the expansion of land use and occupation, thus allowing subsidization of territorial planning policies.